Pemanfaatan Internet sebagai Media Pemasaran Pondok Wisata di Desa Pelaga, Kabupaten Badung - Ni Made Suastini; I Gusti Agung Gede Witarsana; I Wayan Jata; Ni Luh Ketut Sri Sulistyawati; Ni Nyoman Sukerti; Ni Luh Gde Sri Sadjuni (Pusat Penelitian dan Pengabdian Kepada Masyarakat Politeknik Pariwisata Bali, 2021)
Pelaga Village, Badung Regency is famous for its beautiful and natural view. Therefore, the community is very enthusiastic to manage homestay as a means of support. In Pelaga Tourism Village, agro-tourism development has also been carried out centered in the Kiadan environment. However, when the field survey was carried out, there were still obstacles in its management of the homestay. Therefore, training related to accommodation management is needed which will be carried out in stages to improve the community's ability to manage homestay. In 2021, the Hotel Administration Study Program has carried out community service in Pelaga Village, Badung Regency regarding the use of the internet as a marketing tools for homestay in Pelaga Village, Badung Regency.